The structure and musculature of male terminalia in the tribe Xanthorhoini Pierce and related tribes (Lepidoptera: Geometridae: Larentiinae), with particular reference to the Palaearctic and Australian regions - Schmidt, Olga (Zootaxa, 2013)
The musculature of the male genitalia was reviewed for the tribe Xanthorhoini and related tribes (Lepidoptera, Geometridae, Larentiinae). The genitalia morphology of males of 11 species was discussed and illustrated, and nine paired and unpaired genital muscles identified. Muscles m1, m2(10), m5(7), m6(5), m7(6), m8(3) and m21 have similar position in all species considered in the paper. Comparative morphology of the male terminalia and position of extensors of the valvae m3(2) and flexors m4 confirmed the previously uncertain separation of Euphyiini and Scotopterygini. Cataclysmini share musculature characters with the tribe Xanthorhoini. The generic affiliation of Xanthorhoe biriviata (Borkhausen) is questionable considering an unusual location of muscles m4. Generally, the places of attachment of the muscles m3(2) and m4 to the sclerites afford valuable characters for the higher classification of this group.